성인의 신체활동과 스트레스 인지정도: 2017년 국민건강영양조사자료를 이용한 단면연구 - 허재헌(Jaeheon Heo) (Seuteureseu yeon-gu (Online), 2019)
본 연구는 신체활동 유형과 스트레스 인지수준과의 연관성을 탐색하는 서술적 조사연구이다. 국민건강영양조사(2017년)자료를 이용하여 20세 이상 성인(5,624명)의 유산소활동, 근력운동, 걷기 활동량에 따라스트레스 인지수준에 차이가 있는지 분석하였다. 평소 스트레스를 많이 느끼는 사람은 1,539명(27.36%) 였으며, 복합표본 다중로지스틱 회귀분석 결과 일주일에 근력운동을 실천한 날이 더 많은 집단, 그리고 걷는시간이 더 많은 집단에서 스트레스를 높게 느끼는 오즈비가 더 낮았다(p＜0.01). 한편, 유산소활동은 총활동량보다 일에서의 신체활동량이 여가활동에서보다 더많은 경우 높은 스트레스인지수준과 관련 있었다. 스트레스 관리에 유용한 신체활동 프로그램 개발을 위한 심도있는 후속연구가 필요하다. Background: The purpose of this study was to explore the association between the high perceived stress of adults and the types and amounts of their physical activities. Methods: The subjects consisted of 5,624 adults aged 20 and older from the 2017 Korean National Health and Nutrition Examination Survey data. The three types of physical activity (aerobic activity, muscular exercise and walking) were investigated and the amounts of physical activity were calculated with time used in each activity were calculated. To examine the association between the high perceived stress and physical activity, complex samples multiple logistic regression analyses were performed with controlling participants’ demographic and socio-economic, health status and health behavior characteristics. Results: There were 1,539 people (27.36%) in the high stress perceived group, and the subjects in the high stress perceived group seemed to perform less time to walking (weighted mean: 217.23 minutes/ week) than the low or not stress perceived group (weighted mean: 241.09 minutes/week). The proportion of subjects doing muscular exercise 3 or more days in a week seemed to higher in the lower stress perceived group than the high stress perceived group. The multiple logistic regression analyses results showed significant correlations between walking or doing muscular exercise and high-perceived stress (p＜0.01). Additionally, the proportion of activity at work seemed to be a significant factor in the perceived stress level. Conclusions: There appears to be a correlation between physical activity especially muscular activity and perceived stress, such that further studies will lead to improvements in stress management strategies. KCI Citation Count: 7